Limitations in forecasting Middle Eastern dust storms with weather models - Bukowski, Jennie, author; van den Heever, Sue, author (Colorado State University. Libraries, 2017)
Airborne mineral dust has dilatant influences on the atmosphere and local environment: dust aerosols function as cloud condensation and ice nuclei, interact with radiation, fertilize maritime ecosystems, and are harmful to the human respiratory system. In arid regions, dust storms can loft an enormous amount of dust particles into the atmosphere and reduce visibility to near zero. In particular, the Arabian Peninsula reports frequent severe dust outbreaks as a result of strong surface winds, forced either by synoptic dynamics or mesoscale downdrafts, known as haboobs. Current forecast and climate models are run at high enough resolution to simulate synoptic events but still employ convective parameterizations, which are incapable of resolving many mesoscale processes. As such, the prediction of dust storms, specifically the location and timing of haboobs, remains a significant forecasting challenge. To understand the uncertainty introduced in the location and concentration of mineral dust via the use of convective parameterizations, the ratio of convective to non-convective dust events must first be established. This study seeks to identify the origins of regional dust events across the Arabian Peninsula and quantify the relative contributions of synoptic versus mesoscale dust lofting. Here, the Weather Research and Forecasting Model coupled with Chemistry (WRF-Chem) is used to simulate a 2016 summertime dust outbreak over the Arabian Peninsula. Several coarse grid simulations with various convective parameterizations are compared against the same runs with the convective parameterizations turned off, leaving only synoptic sources of dust lofting. These results are then contrasted against a fine grid simulation with resolved convection. For simulations including convection, the inception of individual dust plumes is separated into convective and non-convective source categories. Dust concentrations based on origin are then analyzed with respect to total domain dust abundance as well as horizontal and vertical extent. Results suggest that convective dust lofting over the Arabian Peninsula is a substantial source of dust to the atmosphere, and concentrations differ between simulations with convective parameterizations and those explicitly resolving convection.
Relative contributions of convective and non-convective dust lofting over the Arabian Peninsula
Simulating Middle Eastern dust storms: uncertainty in weather forecast models
Keywords: dust storms; airborne mineral dust; air quality; Middle East